THE SIDER CRUSADE. - Neuhaus, Richard John (First Things: A Monthly Journal of Religion & Public Life, 1992)
Focuses on the issues raised on the arguments raised by author Ron Sider on several social and political issues. Criticisms raised against Sider's analysis of the causes of world hunger discussed in his book "Rich Christians in an Age of Hunger"; Approaches used by Sider in dealing with left-wing publications; Role of the author in evangelical Protestantism.